The development and skills of expert major junior hockey player agents - Hancock, D. J.; Ste-Marie, D. M.; Schinke, R. J. (Talent Development & Excellence, 2010)
Sport scientists have examined expert athletes, coaches, and officials. However, secondary sport participants, such as player agents, have been overlooked. Examining secondary sport participants may provide a better understanding of the development of expertise across all sport participants. The purpose of this study was to examine the development and skills of player agents. Six expert Major Junior hockey player agents were investigated using semi-structured interviews. An expert panel assisted with the interview guide development and data analysis. Results demonstrated that experts progressed through 4 developmental stages (pre-agency years, early years, developmental years, and expert status years) and possessed 4 superior skill sets (recruiting skills, contract skills, player management skills, and business management skills). The implications of the results for player agents and athletes are discussed.